Losses Minyak Pada Stasiun Press di PT. Palmina Utama - Syamsul Rizal; Linda Rahmawati (Agrisains: Jurnal Budidaya Tanaman Perkebunan Politeknik Hasnur, 2021)
The press station is the main station for quoting oil from the pulp of palm oil (CPO). In the screw press, there are several things that need to be considered in order to determine the success of the extraction process, namely the percentage level of oil losses which is one of the benchmarks for the success of extraction at the press station. Some things that can affect the percentage level of oil losses at the press station are the amount of pressure on the press machine and the level of chopping blades in the digester. This observation is carried out by direct observation method at PT. Palmina Utama, using a purposive sampling method.samples taken for the analysis of oil losses at this press station are in the form of fiber, the persentage value of oil losses is determined by exstraction using soxhlet with n-hexane solvent. Samples for analysis were taken from five press machines at the press station in the form of fiber and taken three times each at three points, namely the left side, the middle side and the right side with an interval of two hours, then the samples were mixed and weighed as much as nine to ten gram. The highest oil losses in February were 4.48% and the lowest losses during February were 4.105%. Based on statistical analysis, that F-Count is smaller than F-table 5% and 1%. Thus, pressure does not affect at the percentage of oil losses.